Multi‐objective bat algorithm with time‐varying inertia weights for optimal design of passive power filters set. Issue 7 (1st April 2015) - Yang, Nien‐Che; Le, Minh‐Duy
Abstract : In this study, a novel method is developed to optimise the design of passive power filters (PPFs). The proposed method is based on the famous bat algorithm (BA) and is expected to make the PPF design easier and more effective than conventional trial‐and‐error approaches. Furthermore, the effects of inertia weight variations on the performance of the proposed method are examined. To optimise performance, the most suitable inertia weight, with the best effects, will be selected. For solving multi‐objective optimisation problems, a so‐called external archive is also integrated into the proposed method. A case study of PPF design is also presented to demonstrate the accuracy, efficiency and superiority of the proposed method.